Adsorptive and photocatalytic properties of metal oxides towards arsenic remediation from water: A review. Issue 6 (December 2021) - Gupta, Arijit Dutta; Rene, Eldon R.; Giri, Balendu Shekhar; Pandey, Ashok; Singh, Harinder
Abstract: Presence of arsenic (As) in water is both toxic and carcinogenic and is one of the most widespread problems around the globe. Metal oxides with specific affinities and high surface areas have proved to be promising adsorbents as well as photocatalysts towards arsenic removal from water. Presence of high affinity surface hydroxyl groups coupled with enormous surface area and porous surface morphology have resulted in exceptional high arsenic removal capacities from water. Arsenic removal is accompanied by the mechanisms of surface migration, deprotonation, oxidation, redox reactions, ligand exchange or charge complexations. This review critically analyses the synthesis, application of various heterostructures of metal oxide, possible mechanism towards arsenic removal from water and its usefulness over conventional adsorbents. Future scopes and challenges for robust and economical solutions towards arsenic free water have also been explored. Graphical Abstract: ga1 Highlights: Metal oxides can act as adsorbents and photocatalysts for As removal from water. Presence of high affinity OH - groups with porous morphology facilitate As removal. As removal performances and their mechanisms using metal oxides have been reviewed. Synergistic effects using trimetallic oxides have been included.